PENGARUH PRICE EARNING RATIO (PER), PRICE TO BOOK VALUE (PBV), DEBT TO EQUITY RATIO (DER), RETURN ON ASSET (ROA), TERHADAP RETURN SAHAM DALAM JAKARTA ISLAMIC INDEX - Wiranegara, Yudo Aria; Suyadi, Imam; Handayani, Siti Ragil (Profit: Jurnal Adminsitrasi Bisnis, 2014)
ABSTRACT The stock market is the place to look for funding activities of the company to fund its operations . The main function of the capital market is as a means of capital formation and accumulation of funds for the financing of a company . In order to facilitate the needs of Muslims in Indonesia who have interest in investment in capital market products , then developed Islamic capital markets in accordance with the basic principles of Islam which is expected to add an alternative means of investment in Indonesia in addition to the investment , which is already known and growing banking sector . Islamic stocks are stocks that the operation does not conflict with Islamic law , either the product or its management . Grouping Islamic stocks are in the Jakarta Islamic Index ( JII ) at the Indonesian Stock Exchange ( BEI ) . Getting a return ( profit ) is the main objective of the trading activity of investors in the capital market . Analysis of the company is one of the means used to analyze a stock investor to do by looking at the financial performance assessed with financial ratios . This study aimed to analyze the effect of Price Earning Ratio ( PER ) , Price to Book Value ( PBV ) Debt To Equity Ratio ( DER ) and Return on Assets ( ROA ) on stock returns is incorporated in the Jakarta Islamic Index ( JII ) the period of 2008 â€“ 2012. Â  Keywords : Price Earning Ratio (PER), Price to Book Value (PBV), Debt to Equity Ratio (DER), Return on Asset (ROA), Stock return and Jakarta Islamic Indeks (JII) ABSTRAK Pasar modal merupakan tempat kegiatan perusahaan untuk mencari dana untuk mendanai kegiatan usahanya. Fungsi utama pasar modal adalah sebagai sarana pembentukan modal dan akumulasi dana bagi pembiayaan suatu perusahaan. Dalam rangka memfasilitasi kebutuhan umat Islam di Indonesia yang memiliki minat investasi pada produk-produk pasar modal, maka dikembangkan pasar modal syariah yang sesuai dengan prinsip dasar Islam sehingga diharapkan akan menambah alternatif sarana investasi di Indonesia disamping investasi yang selama ini sudah dikenal dan berkembang disektor perbankan. Saham syariah merupakan saham-saham perusahaan yang dalam operasionalnya tidak bertentangan dengan syariat islam, baik mengenai produk maupun manajemennya. Pengelompokan saham syariah berada dalam Jakarta Islamic Index (JII) di Bursa Efek Indonesia (BEI). Memperoleh return (keuntungan) merupakan tujuan utama dari aktivitas perdagangan para investor di pasar modal. Analisis perusahaan merupakan salah satu cara yang digunakan investor untuk menganalisis suatu saham yang dapat dilakukan dengan melihat kinerja keuangan yang dinilai dengan rasio keuangan. Penelitian ini bertujuan untuk menganalisis pengaruh Price Earning Ratio (PER), Price to Book Value (PBV), Debt To Equity Ratio (DER) dan Return on Asset (ROA) terhadap return saham yang tergabung dalam Jakarta Islamic Index (JII) periode tahun 2008 - 2012 Kata Kunci : Price Earning Ratio (PER), Price to Book Value (PBV), Debt to Equity Ratio (DER), Return on Asset (ROA), Return saham dan Jakarta Islamic Indeks (JII)